2016
DOI: 10.1007/s11356-016-7554-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of morphological and molecular composition changes in allergenic Artemisia vulgaris L. pollen under traffic pollution using SEM and FTIR spectroscopy

Abstract: Nowadays, pollen allergy becomes an increasing problem for human population. Common mugwort (Artemisia vulgaris L.) is one of the major allergenic plants in Europe. In this study, the influence of air pollution caused by traffic on the structure and chemical composition of common mugwort pollen was investigated. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and curve-fitting analysis of amide I profile was applied to assess the morphological and structural changes of mugwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 61 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…In addition to classification and identification studies, vibrational spectroscopies provide biochemical characterization of pollen with respect to environmental conditions. For example, differences in chemical phenotypes of pollen were measured with respect to nutrient availability , heat stress (Lahlali et al, 2014;Jiang et al, 2015), pollution stress (Depciuch et al, 2016(Depciuch et al, , 2017, location (Bagcıoglu et al, 2017;Zimmermann et al, 2017), and season (Zimmermann and Kohler, 2014;Bagcıoglu et al, 2017). In general, Raman and Fourier transform infrared (FTIR) spectroscopies provide chemically complementary information, and therefore measurement of samples by both techniques provides highly detailed biochemical characterization (Zimmermann, 2010;Pummer et al, 2013;Bagcioglu et al, 2015;Zimmermann et al, 2015a;Diehn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to classification and identification studies, vibrational spectroscopies provide biochemical characterization of pollen with respect to environmental conditions. For example, differences in chemical phenotypes of pollen were measured with respect to nutrient availability , heat stress (Lahlali et al, 2014;Jiang et al, 2015), pollution stress (Depciuch et al, 2016(Depciuch et al, , 2017, location (Bagcıoglu et al, 2017;Zimmermann et al, 2017), and season (Zimmermann and Kohler, 2014;Bagcıoglu et al, 2017). In general, Raman and Fourier transform infrared (FTIR) spectroscopies provide chemically complementary information, and therefore measurement of samples by both techniques provides highly detailed biochemical characterization (Zimmermann, 2010;Pummer et al, 2013;Bagcioglu et al, 2015;Zimmermann et al, 2015a;Diehn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In general, FTIR enables fast and economical measurement of samples without any chemical pretreatment. The studies have shown that FTIR spectroscopy is a powerful method for pollen phenotyping because it provides precise identification and chemical characterization with respect to phylogeny and environmental stress (Bağcıoğlu, Kohler, Seifert, Kneipp, & Zimmermann, 2017;Jiang et al, 2015;Lahlali et al, 2014;Zimmermann & Kohler, 2014;Zimmermann et al, 2015b), including influence of anthropogenic stress on chemical composition of pollen (Depciuch, Kasprzyk, Roga, & Parlinska-Wojtan, 2016;Depciuch, Kasprzyk, Sadik, & Parlinska-Wojtan, 2017). However, the use of FTIR spectroscopy to study the genetic and phenotypically plastic components of the chemical composition of pollen and its potential in studies of evolution of male function has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollutants also impact grass pollen. Depending on the plant species and the pollutant type and concentration, such effects may include altered vitality, shape, size, physiologic features, and metabolism of the pollen grain . Motta et al .…”
Section: Discussionmentioning
confidence: 99%